2021
DOI: 10.1002/ange.202114290
|View full text |Cite
|
Sign up to set email alerts
|

Biasing the Hierarchy Motifs of Nanotoroids: from 1D Nanotubes to 2D Porous Networks

Abstract: Hierarchical organization of self-assembled structures into superstructures is omnipresent in Nature but has been rarely achieved in synthetic molecular assembly due to the absence of clear structural rules.W eh erein report on the selfassembly of scissor-shaped azobenzene dyads which form discrete nanotoroids that further organizei nto 2D porous networks.T he steric demand of the peripheral aliphatic units diminishes the trend of the azobenzene dyad to constitute stackable nanotoroids in solution, thus afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…[20][21][22] Recently, inspired by crystallization-driven self-assembly (CDSA) of BCPs in solution, the study of LC-driven self-assembly (LCDSA) has attracted growing interest, which provides a promising alternative methodology to control the morphologies of micelles. [23][24][25] For instance, Liu et al 26 demonstrated that polygonal cylindrical aggregates bearing sharp bends could be formed from LC poly(perfluorooctylethyl methacrylate) (PFOEMA)-containing triblock polymers. In particular, the seeded growth and selfseeding approach, [27][28][29][30] borrowed from the polymer crystallization and living CDSA, can also be used in the LC system to create hierarchical architectures of controlled dimensions and composition, such as branched, hairy plate, and star-like micelles.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Recently, inspired by crystallization-driven self-assembly (CDSA) of BCPs in solution, the study of LC-driven self-assembly (LCDSA) has attracted growing interest, which provides a promising alternative methodology to control the morphologies of micelles. [23][24][25] For instance, Liu et al 26 demonstrated that polygonal cylindrical aggregates bearing sharp bends could be formed from LC poly(perfluorooctylethyl methacrylate) (PFOEMA)-containing triblock polymers. In particular, the seeded growth and selfseeding approach, [27][28][29][30] borrowed from the polymer crystallization and living CDSA, can also be used in the LC system to create hierarchical architectures of controlled dimensions and composition, such as branched, hairy plate, and star-like micelles.…”
Section: Introductionmentioning
confidence: 99%